Theological education and the COVID-19 pandemic in Sub-Saharan Africa: A Malawian perspective - Jones H. Mawerenga; Johannes J. Knoetze (In die Skriflig, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has brought a unique disruptive moment of unprecedented proportions in world history affecting all spheres of life. Theological education in Malawi, Sub-Saharan Africa, has not been spared in experiencing the effects of the COVID-19 pandemic. This study argues that the effectiveness of theological education in Africa contributes towards the future of Christianity on the continent, because it serves as a foundation for a vibrant missional church. Nevertheless, the COVID-19 pandemic has provided opportunities for creativity and innovation which could ensure the survival and sustainability of theological education in Africa. It is therefore crucial to critically reflect on how the provision of theological education in Malawi in particular, and in Sub-Saharan Africa, in general, can be sustained during the uncertain and challenging times when the COVID-19 pandemic is devastating the African continent and the entire world. This article investigated the challenges and opportunities for theological education in Malawi in view of the ongoing COVID-19 pandemic. In view of this, the following five objectives emerged: (1) to evaluate the Malawi government’s response to the COVID-19 pandemic; (2) to discuss the history and importance of theological education in Africa; (3) to examine the challenges of theological education in Malawi in view of the ongoing COVID-19 pandemic; and (4) to assess the prospects of theological education in Malawi in view of the ongoing COVID-19 pandemic. A qualitative research methodology was used, namely a literature review and interviews with members of the faculty of theological institutions in Malawi. Six main findings were established: First, the COVID-19 pandemic has presented both challenges and opportunities for theological education in Africa. Second, the effectiveness of theological education in Africa has contributed towards the future of Christianity on the continent. Third, the COVID-19 pandemic has challenged the dominant models of theological education in Africa. This entails a shift from face-to-face teaching to online teaching and learning. Fourth, the COVID-19 pandemic has provided opportunities for the sustainability of theological education in Africa. Fifth, theological education has encountered misleading theologies regarding the COVID-19 pandemic. Sixth, theological education has the opportunity of constructing life-giving theologies in Africa. This study has two implications: (1) navigating the changing terrain of theological education in Malawi; and (2) theological education’s employment of digital technologies during and post the COVID-19 pandemic.